Chemotherapy for downsizing unresectable liver metastases from colorectal cancer - Robinson, Stuart (Cochrane Database Syst Rev, 2021)
The protocol is out of date and does not meet the current methodological standards of Cochrane. Withdrawn by Cochrane Colorectal group, currently no plans to revise/republish.